Using photovoice to define “community” in substance use disorder research engaging service users, providers, and policymakers - McGladrey Margaret L; Marisa Booty; Ramona Olvera; Peter Balvanz; Hilary L. Surratt; Shannon Matthews; Susannah Stitzer; Owusua Yamoah; Sylvia Ellison; Kevin Campbell; Amy Farmer; Bethany Gealy; et al. (SSM: Qualitative Research in Health)
(197 words)The ideals of community-engaged health research are challenging to realize ethically and methodologically, particularly when focused on substance use disorder (SUD), in which the power differentials inherent to stigma marginalize people with lived experience (LE) as full community participants. This study provides a typology and exploratory data generated through Photovoice to understand relationships among community members with different roles related to LE of SUD (i.e., SUD service providers, service users, and the public) in the context of a large-scale community-engaged opioid overdose reduction intervention. A team of 14 participants and researchers used an adapted thematic analysis method to interpret Photovoice data from 65 total participants in Kentucky, Massachusetts, and Ohio. Photovoice data indicated the influence of stigmatization on perceptions of service users as problems to be solved by service providers without the significant investment of the rest of the community. Service provider burnout is exacerbated by competition for scarce public investments in addressing the dire need for SUD services amid the opioid epidemic. Community-engaged SUD research can be improved by defining the parameters of communities in explicit, participatory, and reflexive ways and recognizing how disinvestment and stigmatization influence relationships among community members occupying different roles in SUD services.